Education on adherence to drug therapy in tuberculosis patients at labuang baji regional public hospital in makassar - Rusman; Sarifah, Latifah Mahaya; Arwana, Arwana; Nursanti, Nursanti; Rumfot, Rabia (Journal of Evidence-Based Community Health, 2024)
Tuberculosis (TB) is a contagious infectious disease caused by the bacteria Mycobacterium tuberculosis, which can attack various organs. Usually attacks the lungs (Pulmonary TB). Tuberculosis (TB) infection is usually spread through the air, namely by coughing, sneezing or splashing saliva from TB sufferers. This community service aims to increase patients' knowledge about TB disease and preventive measures for TB transmission within the Labuang Baji Regional General Hospital. This community service activity was carried out by delivering educational materials and distributing brochures about TB disease to all patients present. The measuring instrument used in this research was a questionnaire. The results of this study show that of the 15 patients who took part in this activity, only 66% of the patients knew what tuberculosis was in the form of the various symptoms that occurred.